2017
DOI: 10.1007/s11845-017-1647-3
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block in combination with posterior capsular infiltration on the pain control after TKA

Abstract: Overall, as compared with ACB or LIA, ACB plus PCI appeared to provide more ideal analgesia and patient satisfaction in the first 24 h after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…LIA is typically employed to reduce post-operative opioid use [4,11,16,22]. Many studies have compared LIA against a nerve block or have examined combined local and regional anesthesia protocols [3,5,10,12,13,20,27,[32][33][34]. Most show no differences, and contradictory results between studies exist.…”
mentioning
confidence: 99%
“…LIA is typically employed to reduce post-operative opioid use [4,11,16,22]. Many studies have compared LIA against a nerve block or have examined combined local and regional anesthesia protocols [3,5,10,12,13,20,27,[32][33][34]. Most show no differences, and contradictory results between studies exist.…”
mentioning
confidence: 99%
“…12 In this current meta-analysis, an analysis of three studies involving 227 patients demonstrated that ACB plus LIA was associated with a significant reduction in morphine consumption during POD 0 and POD 1 compared with isolated ACB. 12,13,16 No significant difference was found between the two groups on POD 2. Postoperative complications are important parameters in comparing the safety of ACB plus LIA and isolated ACB for pain control after TKA.…”
Section: Discussionmentioning
confidence: 74%
“…the included studies are presented in Table 1. [11][12][13][14][15][16] The risk of bias in the RCTs in this study was independently evaluated by two reviewers according to the criteria of the modified Jadad score. The methodological scores of each can range from 0 to 7; a higher score indicates better methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations